Analisis Deskriptif Keseimbangan dan Risiko Jatuh Lansia Berbasis Komunitas di Desa Tohudan - Afif Ghufroni; Jasmine Kartiko Pertiwi (Politeknik Kesehatan Kemenkes Surakarta, 2026)
Background: Falls are a major health problem among older adults and contribute to injury, functional decline, and reduced quality of life. Balance impairment is one of the primary factors associated with fall risk. Early balance screening at the community level is essential to identify older adults at risk and to inform fall prevention strategies. Objectives: This study aimed to describe balance performance and fall risk among older adults in Tohudan Village. Methods: A descriptive observational cross-sectional study was conducted involving 60 community-dwelling older adults aged ≥50 years. Balance performance was assessed using the Berg Balance Scale (BBS). Descriptive statistics were used to summarize participant characteristics and balance scores. Results: The mean age of participants was 64.97±6.50 years, with a mean BBS score of 45.95±2.46. Most participants demonstrated good to moderate balance, although several individuals scored near the fall-risk threshold. Conclusion: Older adults in Tohudan Village generally exhibit adequate balance; however, routine balance screening remains necessary to identify individuals at higher risk of falls and to support community-based preventive interventions. Keywords : Older Adults, Balance, Fall Risk, Berg Balance Scale.